2003
DOI: 10.1103/physrevd.67.073010
|View full text |Cite
|
Sign up to set email alerts
|

Two-loop neutrino mass generation and its experimental consequences

Abstract: If neutrino masses have a radiative origin, their smallness can be naturally understood even when lepton number violation occurs near the weak scale.We analyze a specific model of this type wherein the neutrino masses arise as two-loop radiative corrections. We show that the model admits the near bimaximal mixing pattern suggested by the current neutrino oscillation data. Unlike the conventional seesaw models, these two-loop models can be directly tested in lepton flavor violating decays τ → 3µ and µ → e + γ a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
202
2
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(213 citation statements)
references
References 48 publications
5
202
2
4
Order By: Relevance
“…It is well known the Zee-Babu model is strongly constrained by charged lepton flavor violating (LFV) processes such as µ → eγ or τ → µµµ [47]. The µ-parameter is constrained to be less than about 500 GeV to make the scalar potential stable [46]. The most recent constraints on Zee-Babu model were studied in [48].…”
Section: Implications For Neutrino Physics In Both Z 2 and U(1) B−l Mmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known the Zee-Babu model is strongly constrained by charged lepton flavor violating (LFV) processes such as µ → eγ or τ → µµµ [47]. The µ-parameter is constrained to be less than about 500 GeV to make the scalar potential stable [46]. The most recent constraints on Zee-Babu model were studied in [48].…”
Section: Implications For Neutrino Physics In Both Z 2 and U(1) B−l Mmentioning
confidence: 99%
“…The U(1) B−L symmetry is spontaneously broken after ϕ obtains vacuum expectation value (vev). In [46], it was shown that µ hk < O(1) m h + to make the scalar potential stable. In this U(1) B−L model, this can be always guaranteed by taking small λ µ , since µ hk = λ µ v ϕ even for very large v ϕ .…”
Section: Jhep09(2014)153mentioning
confidence: 99%
See 1 more Smart Citation
“…The neutrino mass is generated radiatively. The additional suppression is guaranteed by a combination of loop integrals [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and EW-scale masses entering the diagrams.…”
Section: Introductionmentioning
confidence: 99%
“…The breaking of lepton number is communicated radiatively to the fermion sector and gives rise to Majorana neutrino masses at the two-loop level. The resulting neutrino spectrum has been compared to the oscillation data in [13]. We would like to investigate a scale-invariant version of Babu's model.…”
Section: Babu Modelmentioning
confidence: 99%